2005
DOI: 10.1292/jvms.67.961
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Magnetic Resonance Imaging on the Brain in Beagle Dogs with Aging

Abstract: ABSTRACT. Age-associated changes of magnetic resonance imaging (MRI) on the brain were evaluated in 19 beagle dogs aged from 8-month-to 16-year-old. A significant correlation of the volume of lateral ventricle space was observed in the dogs with age advanced, however, no correlation was found between hippocampus size and the aging. The hypo-intensity areas on T2-weighted MRI were detected in globus pallidus and substantia nigra with a significant correlation of both intensity ratios to lateral ventricle with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 36 publications
5
45
0
Order By: Relevance
“…The flash VEP recorded in dogs showed 3 positive (P1, P2 and P3) and 2 negative (N1 and N2) components by 150 msec after the flash stimuli, like as those reported in human [11,17,19]. In addition, various age-associated pathological and/or physiological changes were commonly observed in aged dogs as well as aged human [5,10]. Since there are few diagnostic techniques for dementia in dogs, age-associated changes of the flash VEP were evaluated using various aged beagle dogs.…”
supporting
confidence: 67%
“…The flash VEP recorded in dogs showed 3 positive (P1, P2 and P3) and 2 negative (N1 and N2) components by 150 msec after the flash stimuli, like as those reported in human [11,17,19]. In addition, various age-associated pathological and/or physiological changes were commonly observed in aged dogs as well as aged human [5,10]. Since there are few diagnostic techniques for dementia in dogs, age-associated changes of the flash VEP were evaluated using various aged beagle dogs.…”
supporting
confidence: 67%
“…There are different reports that have distinguished the MR signs in dogs with hydrocephalus, cerebellar degeneration, necrotizing encephalitis, granulomatous meningoencephalitis, infarcts, age-related degeneration, spinal cord hernias, wobbler syndrome, arachnoid cysts, syringohydromyelia associated with Chiari-like malformation in the Cavalier King Charles spaniel (Fig. 1), discospondylitis, atlantoaxial instability, meningeal calcification, hydromyelia, mechanical damage, and brain and spinal tumors (Vullo et al 1997, Gonzalo-Orden et al 2000, Kimotsuki et al 2005, Besalti et al 2006, Garosi et al 2006, Okada et al 2006, Matiasek et al 2007, Couturier J et al 2008, Sturges et al 2008, Carrera et al 2009, Cerda-Gonzalez S et al 2009, Young et al 2009, Gavin PR 2011.…”
Section: Indicationsmentioning
confidence: 99%
“…However, they are not commonly used for the prediction, diagnosis or follow-up of canine aging with cognitive dysfunction. The relationship between progressive canine brain atrophy and aging has been evidenced in several post-mortem studies [40][41][42] and recently confirmed in housed dogs, frequently beagles, using a variety of MRI techniques [43,44]. To determine whether progressive global cerebral atrophy is a marker of aging in dogs as well as in humans, an MRI study in companion dogs was performed with an adapted version of a simple human visual rating assessment (Fig.2).…”
Section: Magnetic Resonance Imaging Techniques and Agingmentioning
confidence: 99%